Trans-Disciplinary Model Of The Team Approach In The Process Of Treatment And Medical And Social Support Of Patients With Alopecia - Aymedov, Сonstantin; Zhivilko, Vladimir; Moldavskya, Khristina (Psychiatry, Neurology and Medical Psychology, 2017)
The article considers the multifactor nature of such a disease as alopecia. It was noted that, despite the complexity and step-by-step measures for alopecia patients, given in the standard clinical protocol, the treatment did not take into account the psychosomatic nature of the disease, as well as the psychosocial predicators of this pathology, its influence on the emotional and personal aspects of patients' lives, their social sphere functioning and quality of life. The authors draw attention to the fact that the clinical protocol requires complementation by introducing a psychosocial component at all stages: diagnosis, treatment, rehabilitation and prevention. The paper describes the results of the implementation of the developed author's program based on the trans-disciplinary model of the team approach, which represents a single consistent phased system of complementary therapeutic, psycho-corrective and psycho-preventive effects in the treatment and medico-social support of the patient with alopecia